1974
DOI: 10.1002/1097-0142(197405)33:5<1451::aid-cncr2820330531>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

The quality of survival in breast cancer: A case-control comparison

Abstract: Quality of survival as defined by physical and psychosocial criteria was found to be remarkably similar among 134 breast cancer patients and 260 controls. Most of the cases had been diagnosed 5 or more years prior to this study. Physical disability was reported by 19% of the cases and 16% of the controls. The slight excess of disability among the cases was related to surgical treatment. There was no evidence of increased psycho‐social disability among the cases. The principal effect of breast cancer was to tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

1977
1977
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(20 citation statements)
references
References 13 publications
2
17
0
1
Order By: Relevance
“…Two studies comparing the employment status of healthy controls versus breast cancer [19] and Hodgkin's disease [77] survivors found no statistically significant differences. Other authors have reported that about 20-25% of cancer survivors were not able to return to work at the same level as a result of having been treated for malignancy [43,44,69].…”
Section: Employment Issues Familial and Social Relationshipsmentioning
confidence: 97%
“…Two studies comparing the employment status of healthy controls versus breast cancer [19] and Hodgkin's disease [77] survivors found no statistically significant differences. Other authors have reported that about 20-25% of cancer survivors were not able to return to work at the same level as a result of having been treated for malignancy [43,44,69].…”
Section: Employment Issues Familial and Social Relationshipsmentioning
confidence: 97%
“…Most are lengthy and require specially trained personnel to use them but they may be valuable in oncological research for detailed study of particular aspects of patients' lives (Maguire et al, 1980;McArdle et al, 1981). Fewer attempts have been made to produce instruments specifically for use in oncological research or practice (Priestman & Baum, 1976;Eisenberg & Goldenburg, 1966;Izsak & Medelie, 1971;Worden & Weisman, 1977;Padilla et al, 1981;Craig et al, 1974), and most of these have not been formally evaluated or widely used. Priestman & Baum (1976) designed an instrument with 10 (and later 25) items (Baum et al, 1980) selected on the basis of their clinical experience and measured by linear analogue self assessment.…”
Section: Correlations Between Scores For Items Within Thementioning
confidence: 99%
“…3 However, in general, studies have found that a cancer survivor's quality of life typically returns to a level comparable to that of individuals with no history of cancer soon after treatment completion. [3][4][5][6] Although the psychosocial functioning of the majority of cancer survivors has not been found to differ significantly from that of the general population, research suggests that a notable percentage of survivors do continue to experience elevated levels of emotional distress. 7 Anxiety, depression, fears of disease recurrence, and concerns regarding passing the disease on to their offspring surface as persistent emotional and psychologic issues of cancer survivors.…”
mentioning
confidence: 99%